Cinema and the Cultural Cold War : US Diplomacy and the Origins of the Asian Cinema Network - Lee, Sangjoon (Book collections on Project MUSE., 2020)
"This book explores the ways in which postwar Asian cinema was shaped by transnational collaborations and competitions between newly independent and colonial states at the height of Cold War cultural politics"--